A pragmasemantic analysis of lexical ambiguity in the Nigeria criminal code act - Muhammad Jamiu Salih Alagolo (Yayasan Mitra Persada Nusantara, 2026)
Legal language tend to be prone to imprecision and multiplicity of meanings which may result in interpretive difficulties and inconsistent judicial outcomes. Despite that, it is observed that the Criminal Code Act (Chapter C38, Laws of the Federation of Nigeria), contains lexical ambiguity which may undermine legal certainty and effective justice delivery. This study investigates such ambiguities by identifying lexically ambiguous expressions in selected provisions. It analyses the ambiguities through Pustejovsky’s semantic qualia structure, and examines the role of pragmatic context using Gricean maxims. The study adopts a qualitative approach with purposive sampling of statutory provisions and judicial interpretations. It employs textual analysis combining semantic and pragmatic frameworks. Findings reveal that lexical ambiguity is pervasive, particularly in provisions central to criminal liability, and that violation of pragmatic principles, clarity, relevance, and sufficiency, contribute to interpretive inconsistencies. The study concludes that lexical ambiguity remains a significant source of legal indeterminacy and recommends the integration of pragma-semantic insights into legislative drafting, alongside interdisciplinary collaboration, to enhance clarity and promote effective justice delivery.